Studi Eksperimental Karakteristik Hambatan Kekentalan Fluida Pada Material Karbon Aktif Bambu Betung Dengan Variasi Temperatur Karbonisasi - Indra Putra, Gede Ogie; Wijaksana, Hendra; Prananda Surya, I Gede Teddy (Teknik Desain Mekanika, 2024)
Abstract Currently, many air conditioning systems are compressor-based, which has caused the use of electrical energy to increase. The cooling machines mentioned above, which use refrigerants as working fluids, also trigger an increase in environmental damage and cause global warming. The direct evaporative cooling system is a cooling pad, which is a wet medium where air and water come in contact. Most of the cooling pad materials used are materials that require wetting using a pump. In this study will examine specifically how the characteristics of the fluid viscosity resistance by using water working fluid to determine the drag force that occurs in the pore material on the betung bamboo material, later betung bamboo active carbon material will be produced with porosity and pore distribution to analyze how the characteristics of the viscosity resistance betung bamboo material fluid that has gone through the process of carbonization and activation without holding time. By using three variables, namely carbonization independent variables with temperature variations of 400°C, 500°C, 600°C, 700°C and 800°C. The dependent variable is the fluid viscosity resistance characteristics. And the control variable is activated with a temperature of 600°C (without holding time). After doing research, the activated carbon material of betung bamboo with QRC800 code produces the smallest drag force, namely 4.36x10-7 N with a minimum capacity of only 0.87x10-10 m3 but has the highest capillary rise of 7.61 m. while the bamboo betung activated carbon material with QRC500 code produces the largest drag force of 7.12x10-7 N with the largest fluid volume capacity of 1.42x10-10 m3 but has the lowest capillary rise rate of only 4.66 m. Betung bamboo activated carbon material with a larger pore diameter, will produce a large drag force and also has a greater capacity with a lower capillary rise than a smaller pore diameter. Keywords: capilary rise, resistance, carbonization, carbon material, bamboo, without holding time